Identifying patients and clinical scenarios for use of long-acting injectable antipsychotics – expert consensus survey part 1 - Sajatovic M (Dove Medical Press, 2018)
Martha Sajatovic,1,2 Ruth Ross,3 Susan N Legacy,4 Christoph U Correll,5,6 John M Kane,5,6 Faith DiBiasi,7 Heather Fitzgerald,8 Matthew Byerly9 1Department of Psychiatry, University Hospitals Cleveland Medical Center, Cleveland, OH, USA; 2Departments of Psychiatry and Neurology, Case Western Reserve University School of Medicine, Cleveland, OH, USA; 3Ross Editorial, Port Townsend, WA, USA; 4US Medical Affairs Neuroscience, Otsuka Pharmaceutical Development & Commercialization, Inc., Princeton, NJ, USA; 5Psychiatry, The Zucker Hillside Hospital, Glen Oaks, NY, USA; 6Psychiatry, The Donald and Barbara Zucker School of Medicine at Hofstra/Northwell, Glen Oaks, NY, USA; 7Scientific Communications, Otsuka Pharmaceutical Development & Commercialization, Inc., Rockville, MD, USA; 8Medical Affairs, Lundbeck LLC, Deerfield, IL, USA; 9Cell Biology and Neuroscience, Center for Mental Health Research and Recovery, Montana State University, Bozeman, MT, USA Objective: To assess expert consensus on barriers and facilitators for long-acting injectable antipsychotic (LAI) use and provide clinical recommendations on issues where clinical evidence is lacking, including identifying appropriate clinical situations for LAI use. Methods: A 50-question survey comprising 916 response options was distributed to 42 research experts and high prescribers with extensive LAI experience. Respondents rated options on relative appropriateness/importance using a 9-point scale. Consensus was determined using chi-square test of score distributions. Mean (standard deviation) ratings were calculated. Responses to 29 questions (577 options) relating to appropriate patients and clinical scenarios for LAI use are reported. Results: Recommendations aligned with research on risk factors for nonadherence and poor outcomes for patients with schizophrenia/schizoaffective or bipolar disorder. Findings suggested, contrary to general practice patterns, that LAI use may be appropriate earlier in the disease course and in younger patients. Results for bipolar disorder were similar to those for schizophrenia but with less consensus. Numerous facilitators of LAI prescribing were considered important, particularly that LAIs may reduce relapses and improve outcomes. Conclusion: Findings support wider use of LAIs in patients with schizophrenia/schizoaffective and bipolar disorders beyond the setting of poor adherence and earlier use in the disease course. Keywords: expert consensus, schizophrenia, schizoaffective disorder, bipolar disorder, long-acting injectable antipsychotics